2013
DOI: 10.1128/jvi.01283-13
|View full text |Cite
|
Sign up to set email alerts
|

The Membrane-Proximal “Stem” Region Increases the Stability of the Flavivirus E Protein Postfusion Trimer and Modulates Its Structure

Abstract: The flavivirus fusion protein E contains a "stem" region which is hypothesized to be crucial for driving fusion. This sequence element connects the ectodomain to the membrane anchor, and its structure in the trimeric postfusion conformation is still poorly defined. Using E trimers of tick-borne encephalitis virus with stem truncations of different lengths, we show that the Nterminal part of the stem increases trimer stability and also modulates the trimer structure outside the stem interaction site. Flavivirus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 28 publications
2
24
0
Order By: Relevance
“…We designed the insertion of miRNA target sequences in this region using an approach that has been described previously by Bonaldo et al (Bonaldo et al, 2007) for generation of recombinant yellow fever viruses expressing foreign genes (Trindade et al, 2012). The C-terminal stem-anchor (SA) region of protein E (~100 amino acid residues) contains four alpha-helices, two of which (H1 and H2) form a stem region, and two amphipathic anti-parallel α-helices (TM1 and TM2) serve as an E protein membrane anchor and as an internal signal sequence for the cellular signal peptidase cleavage during polyprotein processing (Fritz et al, 2011; Pangerl et al, 2011; Stiasny et al, 2013). Three tandem target sequences for miRNAs were placed between sequences encoding the two SA domains: the first SA domain, located upstream of the miRNA-targets, was a part of the TBEV E protein; the second SA domain, located downstream of the miRNA targets, contained the sequence from the DEN4 E protein (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We designed the insertion of miRNA target sequences in this region using an approach that has been described previously by Bonaldo et al (Bonaldo et al, 2007) for generation of recombinant yellow fever viruses expressing foreign genes (Trindade et al, 2012). The C-terminal stem-anchor (SA) region of protein E (~100 amino acid residues) contains four alpha-helices, two of which (H1 and H2) form a stem region, and two amphipathic anti-parallel α-helices (TM1 and TM2) serve as an E protein membrane anchor and as an internal signal sequence for the cellular signal peptidase cleavage during polyprotein processing (Fritz et al, 2011; Pangerl et al, 2011; Stiasny et al, 2013). Three tandem target sequences for miRNAs were placed between sequences encoding the two SA domains: the first SA domain, located upstream of the miRNA-targets, was a part of the TBEV E protein; the second SA domain, located downstream of the miRNA targets, contained the sequence from the DEN4 E protein (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Both stem (H1 and H2 helices) and transmembrane anchor (TM1 and TM2 helices) regions are believed to be involved and play an active role in the formation of the E protein trimer and the fusion to endosomal membrane during virus entry into the cell (Fritz et al, 2011; Pangerl et al, 2011; Stiasny et al, 2013). Fritz et al (Fritz et al, 2011) recently demonstrated that the TM1 and/or TM2 regions of the TBEV E protein can be substituted by the corresponding sequences derived from a distantly related flavivirus (Japanese encephalitis virus), but this resulted in dramatic reduction of virus growth in mammalian cells.…”
Section: Discussionmentioning
confidence: 99%
“…in Drosophila Schneider 2 (S2) cells (Invitrogen) with an enterokinase cleavage site and a strep-tag. The pT389-sE400 [41], pT389-sE419 [28], and pT389-sE448 [28] expression plasmids were already available. The pT389-sE401 expression plasmid was generated by mutagenesis of the pT389-sE400 clone (GeneArt site-directed mutagenesis system, Invitrogen) following the manufacturer's instructions.…”
Section: Cloning Proceduresmentioning
confidence: 99%
“…Recombinant proteins after enterokinase cleavage (sE400r, sE401r, sE404r, sE408r, sE412r, sE419r, sE428r) as well as the virion-derived sE401v [45] were converted into trimers under acidic pH conditions in the presence of liposomes as described previously [28][29][30]. Fifteen nanomoles of lipids per microgram sE was mixed and acidified by the addition of 350 mM morpholineethanolsulfonic acid (MES).…”
Section: Trimer Preparationsmentioning
confidence: 99%
“…X-ray crystallography studies [1] have shown that the structure of the soluble part of E consists of three domains and includes the fusion loop, which is critical for fusion of the host and viral membranes and putative receptor-binding region. The membrane-associated region of E includes an α-helical segment known as the “stem” region, which has also been shown to be critical for membrane fusion [2] , [3] , along with two transmembrane helices that anchor E to the viral membrane. The PrM protein consists of a globular domain that “caps” the fusion loop of E to prevent premature fusion [4] , a linker region containing a furin cleavage motif, and an α-helical membrane-associated region, including two transmembrane helices.…”
Section: Introductionmentioning
confidence: 99%